Between Myth and Reality: The Palestinian Political Elite and the Two-State Solution. Issue 2 (November 2014) - Naser-Najjab, Nadia
<x xml:space="preserve">Abstract</x> Although the two-state solution originated as a concession to preponderant political realities (specifically Israeli military superiority and international political pressures), it has subsequently become detached from any semblance of reality. While the two-state framework remains an article of faith for the Palestinian leadership, the day-to-day existence of West Bank Palestinians approximates more closely with an apartheid (one-state) reality. In interrogating this Janus-faced construction, the subsequent article seeks to establish whether the peace process should be re-interpreted as a manifestation of deeper divides and splits within the Palestinian body politic